Beginner Haskell: Making a last function with reverse - function

I'm attempting to make a function that generates the last item in a list. I want to use reverse and !!. This is what I have so far:
myLast :: [a] -> [a] -> Int -> a
myLast xs = (reverse xs) !! 1
I know the problem lies somewhere within the type, but I'm having trouble identifying how to fix it.

A function's type signature has nothing to do with what you use in the function, it only describes how other people can use this function you're defining. So by writing
myLast :: [a] -> [a] -> Int -> a
you're saying, users need to supply two lists and and integer. Just to get the last element of one of the lists?? That doesn't make sense.
You surely mean
myLast :: [a] -> a
You should generally write that down before even thinking about how you're going to implement that function.
With that signature, you can write various implementations:
myLast :: [a] -> a
myLast xs = head $ reverse xs
myLast' :: [a] -> a
myLast' [l] = l
myLast' (_:xs) = myLast' xs
myLast'' :: [a] -> a
myLast'' = fix $ \f (x:xs) -> maybe x id . teaspoon $ f xs
or whatever weird implementation you choose, it has nothing to do with the signature.
On an unrelated note: though last is actually a standard function from the prelude, it's a kind of function avoided in modern Haskell: last [] gives an error, because the is no a value to be found in the empty list! Errors are bad. Hence the “ideal” way to write it is actually
myLast :: [a] -> Maybe a
myLast [] = Nothing
myLast [x] = x
myLast (_:xs) = myLast xs

I would recommend not using !! at all, but to use head.
myLast xs = head (reverse xs)
Head returns the first element of the list it is given as argument.
If you insist on using !!, in Haskell arrays are indeed zero-based, which means that !! 0 gets the first element, !! 1 the second, etc.
As for the type: myLast takes an array of some type and returns one item of that same type. That is denoted as follows:
myLast :: [a] -> a
#leftaroundabout covered this way better in his answer.

Based on #leftaroundabout 's answer, here's an implementation that should do what you want:
safeHead :: [a] -> Maybe a
safeHead [] = Nothing
safeHead (x:_) = Just x
myLast :: [a] -> Maybe a
myLast [] = Nothing
myLast xs = safeHead $ reverse xs
The Maybe type is constructed as follows (from Hackage):
data Maybe a = Nothing | Just a
deriving (Eq, Ord)
myLast [1, 2, 3, 4], for example, will return Just 4. If you want to use the value 4 you can use the function fromJust function from the Data.Maybe module (fromJust (Just 4) returns 4). fromJust is defined like this:
-- | The 'fromJust' function extracts the element out of a 'Just' and
-- throws an error if its argument is 'Nothing'.
--
-- ==== __Examples__
--
-- Basic usage:
--
-- >>> fromJust (Just 1)
-- 1
--
-- >>> 2 * (fromJust (Just 10))
-- 20
--
-- >>> 2 * (fromJust Nothing)
-- *** Exception: Maybe.fromJust: Nothing
--
fromJust :: Maybe a -> a
fromJust Nothing = error "Maybe.fromJust: Nothing" -- yuck
fromJust (Just x) = x

Related

Explanation of map functions (using foldr) in Haskell?

I'm trying to define the map function using foldr
I have found the two following solutions, however I'm not quite sure how they are working.
map' :: (a -> b) -> [a] -> [b]
map' f = foldr ((:) . f) []
map'' :: (a -> b) -> [a] -> [b]
map'' f = foldr (\x xs -> f x : xs) []
I'm quite new to Haskell and foldr, so I'm struggling to understand what ((:) . f) in the first solution and what (\x xs -> f x : xs) in the second solution do.
I also don't get how foldr is able handle the empty list case.
It would be much appreciated if I could get a simple step by step explanation of this, in layman's terms.
Both (\x xs -> f x : xs) and (:) . f mean the same thing. They're both functions that take two arguments, apply f to the first argument, and then cons that onto the second argument.
So what does foldr do when given an empty list? It simply returns the starting value, which in these examples is [].
Here is the implementation of foldr from Hackage:
foldr k z = go
where
go [] = z
go (y:ys) = y `k` go ys

Haskell-- Trying to make my foldl function work

I have a function that converts [a, b, c, d, . . . ] to [(a,b), (c, d), . . .]. Now this works and here is the code for that:
makeTuple :: [a] -> [(a,a)]
makeTuple [] = []
makeTuple [a] = []
makeTuple (x:y:xs) = (x,y): (makeTuple xs)
Now the next thing I have to do is this: Using the previous function, convert each tuple to a product of its two elements, using foldl and a lambda expression. And this is what I have:
productTuple [x] = foldl makeTuple [] [x]
Now I am not sure if this is exactly what is being asked of me. I'm not sure if I should make a separate function with the type declaration and whatnot. Maybe someone can tell me if that is the best way to approach this. Also this code does not work, and I don't know why,I need help with this part. (notice that it says to use a lambda, but I have no idea how to really properly use those, which is another part I need help with) I would really appreciate it, thanks.
The lambda function should respect this signature :
[a] -> (b,b) -> [a]
The accumulator has the type [a], the tuple has the type (b,b)
You can try a lambda like this \acc (a, b) -> acc++[a*b]
The final function could look like :
productTuple :: Num a => [a] -> [a]
productTuple xs = foldl (\acc (a, b) -> acc++[a*b]) [] (makeTuple xs)
You have some examples of foldl function here
I tried this code here
The exercise is asking you to preprocess the input lists with the makeTuple, and then fold over it.
productTuple :: [Int] -> [Int]
productTuple xs = foldl (some lambda) something (makeTuple xs)
It is not the most convenient way to do it, but I guess that the point of the exercise is to force you to use foldl just for the sake of it.

Replacing functions in composite function in haskell

I'm trying to become familiar with Haskell and I was wondering if the following was possible and if so, how?
Say I have a set of functions {f,g,..} for which I was to define a replacement function {f',g',..}. Now say I have a function c which uses these functions (and only these functions) inside itself e.g. c x = g (f x). Is there a way to automatically define c' x = g' (f' x) without explicitly defining it?
EDIT: By a replacement function f' I mean some function that is conceptually relates to f by is altered in some arbitrary way. For example, if f xs ys = (*) <$> xs <*> ys then f' (x:xs) (y:ys) = (x * y):(f' xs ys) etc.
Many thanks,
Ben
If, as seems to be the case with your example, f and f' have the same type etc., then you can easily pass them in as extra parameters. Like
cGen :: ([a] -> [a] -> [a]) -> (([a] -> [a]) -> b) -> [a] -> b
cGen f g x = g (f x)
...which BTW could also be written cGen = (.)...
If you want to group together specific “sets of functions”, you can do that with a “configuration type”
data CConfig a b = CConfig {
f :: [a] -> [a] -> [a]
, g :: ([a] -> [a]) -> b
}
cGen :: CConfig a b -> [a] -> b
cGen (CConfig f g) = f . g
The most concise and reliable way to do something like this would be with RecordWildCards
data Replacer ... = R {f :: ..., g :: ...}
c R{..} x = g (f x)
Your set of functions now is now pulled from the local scope from the record, rather than a global definition, and can be swapped out for a different set of functions at your discretion.
The only way to get closer to what you want would to be to use Template Haskell to parse the source and modify it. Regular Haskell code simply cannot inspect a function in any way - that would violate referential transparency.

Using an element against an entire list in Haskell

I have an assignment and am currently caught in one section of what I'm trying to do. Without going in to specific detail here is the basic layout:
I'm given a data element, f, that holds four different types inside (each with their own purpose):
data F = F Float Int, Int
a function:
func :: F -> F-> Q
Which takes two data elements and (by simple calculations) returns a type that is now an updated version of one of the types in the first f.
I now have an entire list of these elements and need to run the given function using one data element and return the type's value (not the data element). My first analysis was to use a foldl function:
myfunc :: F -> [F] -> Q
myfunc y [] = func y y -- func deals with the same data element calls
myfunc y (x:xs) = foldl func y (x:xs)
however I keep getting the same error:
"Couldn't match expected type 'F' against inferred type 'Q'.
In the first argument of 'foldl', namely 'myfunc'
In the expression: foldl func y (x:xs)
I apologise for such an abstract analysis on my problem but could anyone give me an idea as to what I should do? Should I even use a fold function or is there recursion I'm not thinking about?
The type of foldl is
foldl :: (a -> b -> a) -> a -> [b] -> a
but the type of func is
-- # a -> b -> a
func :: F -> F -> Q
The type variable a cannot be simultaneously F and Q, thus the error.
If the Q can be converted to and from F, you could use
myfunc y xs = foldl (func . fromQ) (toQ y) xs
where
func . fromQ :: Q -> F -> Q
toQ y :: Q
xs :: [F]
so this satisfies all the type requirements, and will return the final Q.
maybe you need map?
map :: (f -> q) -> [f] -> [q]
it evaluates a function on each element in a list and gives a list of the results. I'm not sure why your function takes two Fs though, possibly to work with foldl?

Function application: Why is $ used here?

A while ago, I asked a question about $, and got useful answers -- in fact, I thought I understood how to use it.
It seems I was wrong :(
This example shows up in a tutorial:
instance Monad [] where
xs >>= f = concat . map f $ xs
I can't for the life of me see why $ was used there; ghci isn't helping me either, as even tests I do there seem to show equivalence with the version that would simply omit the $. Can someone clarify this for me?
The $ is used here because it has lower precedence than normal function application.
Another way to write this code is like so:
instance Monad [] where
xs >>= f = (concat . map f) xs
The idea here is to first construct a function (concat . map f) and then apply it to its argument (xs). As shown, this can also be done by simply putting parenthesis around the first part.
Note that omitting the $ in the original definition is not possible, it will result in a type error. This is because the function composition operator (the .) has a lower precedence than normal function application effectively turning the expression into:
instance Monad [] where
xs >>= f = concat . (map f xs)
Which doesn't make sense, because the second argument to the function composition operator isn't a function at all. Although the following definition does make sense:
instance Monad [] where
xs >>= f = concat (map f xs)
Incidentally, this is also the definition I would prefer, because it seems to me to be a lot clearer.
I'd like to explain why IMHO this is not the used style there:
instance Monad [] where
xs >>= f = concat (map f xs)
concat . map f is an example of so-called pointfree-style writing; where pointfree means "without the point of application". Remember that in maths, in the expression y=f(x), we say that f is applied on the point x. In most cases, you can actually do a final step, replacing:
f x = something $ x
with
f = something
like f = concat . map f, and this is actually pointfree style.
Which is clearer is arguable, but the pointfree style gives a different point of view which is also useful, so sometimes is used even when not exactly needed.
EDIT: I have replaced pointless with pointfree and fixed some examples, after the comment by Alasdair, whom I should thank.
The reason $ is used here is doe to the type signature of (.):
(.) :: (b -> c) -> (a -> c) -> a -> c
Here we have
map f :: [a] -> [[b]]
and
concat :: [[b]] -> [b]
So we end up with
concat . map f :: [a] -> [b]
and the type of (.) could be written as
(.) :: ([[b]] -> [b]) -> ([a] -> [[b]]) -> [a] -> [b]
If we were to use concat . map f xs, we'd see that
map f xs :: [[b]]
And so cannot be used with (.). (the type would have to be (.) :: (a -> b) -> a -> b